Seeking “Mamatowisowin” to Create an Engaging Social Policy Class for Aboriginal Students - Faith, Erika (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2007)
This article recounts the author’s personal and professional journey of developing a social policy social work course at the First Nations University of Canada. With no social policy text designed for and about Aboriginal peoples, and very few articles written on social policy issues in Aboriginal communities, the author was challenged to create content, pedagogy, and assignment structures that reﬂected the cultures of her students who come primarily from the plains and woodlands reserve communities of Saskatchewan. By consulting with Elders, colleagues, and students, as well as by paying attention to her own internal sense of stress or delight, she progressively modiﬁed the class over three years, releasing all that was‘dry and detached’ while building on all that was fun, relevant and exciting. Along the way, the author was introduced to the néhiyawéwin (Cree) word mamatowisowin, which refers to a state of spiritual attunement and divine inspiration. I realized that, perhaps more than head knowledge, it was mamatowisowin that she most needed in order to create a class that optimally served her students and the university’s vision of a ‘bicultural education’ that is equally grounded in both European and Indigenous knowledge systems.